FINANCIAL CRITICAL SUCCESS FACTOR OF PSN SPAM PROJECT MANAGEMENT, REGIONAL JATILUHUR PHASE 1 - Tampubolon, Andre; Pontan, Darmawan (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
Research analyzing Non-Technical Critical Success Factors, especially those related to finance, has not been widely conducted in the field of construction management in developing countries such as Indonesia. This study aims to describe the financial critical success factors of the Jatiluhur Regional SPAM PSN Project Management Phase 1 and to analyze which factors are most dominant. The current study only focuses on the financial aspects of the project CSFs, namely Project Related Factors, Business and Work Environment Related Factors, Client Related Factors, and Project Management Factors. Primary research data were collected through an AHP questionnaire distributed to 5 key informants. The results of the analysis of the financial critical success factors of the Jatiluhur Regional SPAM PSN Project Management Phase 1 show that project-related factors have the highest weight (0.588), followed by client-related factors (0.175), the next factor is project management factors (0.133), land transfer pricing (0.070), and finally business and work environment-related factors. The results of the weighting analysis of the financial critical success factor sub-factors of the Jatiluhur Regional SPAM PSN Project Management Phase 1 showed that the project capital composition sub-factor ranked first in terms of overall importance of the CSF sub-factors of the Jatiluhur Regional SPAM PSN Project Management Phase 1, with a weighting of 0.270 (27%).